Susceptibility of fifth instar nymphs of Rhodnius prolixus (Hemiptera: Reduviidae) to the action of the fungus Beauveria bassiana - VÁSQUEZ P., CARMEN A.; SALDARRIAGA-O., YAMILLÉ; CHAVERRA-R., DUVERNEY (Revista Colombiana de Entomología, 2005)
The effect of the entomopathogenic fungus Beauveria bassiana (strain UdeA13) was evaluatedon fifth instar nymphs of Rhodnius prolixus under laboratory conditions. The strain was isolated from R. pallescens in the region of San Onofre (Sucre) and cultivated on Sabouraud Dextrosa Agar (SDA). Theinsect colonies were propagated and reared under controlled conditions of temperature (25-27ºC) and relative humidity (80%) in darkness for growth and reproduction. The insects were feed weekly for 1 h with hen´s blood (Gallus gallus). The treatments consisted of conidial suspensions of the entomopathogenic fungus B. bassiana at concentrations of 3x105, 1x107, 3x108 and 3x109 conidia/ml which were sprayed on the insects using the Pulverization Tower emulator system. Control insects were sprayed with an aqueous solution of Tween 80 (0,01%). Effects were compared among fungus treatments and the controls. Significative differences (P